2015
DOI: 10.1007/s13197-015-1954-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guar gum and xanthan gum on pasting and noodle-making properties of potato, corn and mung bean starches

Abstract: The effect of xanthan and guar-gum on pasting and noodle-making properties of potato, corn and mung bean starches was studied. Mung bean starch showed the highest amylose content (43.4 %) followed by potato (23.2 %) and corn starch (15.5 %). Potato starch showed the highest swelling power (19.0 g/g) and solubility index (17.5 %) and exhibited the highest paste viscosities. Addition of both gums improved peak viscosity, hot paste viscosity and final viscosity for mung and corn starches; while for potato starch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 31 publications
11
106
1
4
Order By: Relevance
“…Flour suspensions (10 %) were held at 50°C for 1 min then heated from 50 to 95°C at a rate of 12.16°C/min, held at 95°C for 2.5 min, cooled from 95 to 50°C at a rate of 11.84°C/min, and held at 50°C for 2 min (Kaur et al 2015a). Parameters recorded were pasting temperature (PT), peak viscosity (PV), breakdown viscosity (BDV), final viscosity (FV), and setback viscosity (SBV).…”
Section: Pasting Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Flour suspensions (10 %) were held at 50°C for 1 min then heated from 50 to 95°C at a rate of 12.16°C/min, held at 95°C for 2.5 min, cooled from 95 to 50°C at a rate of 11.84°C/min, and held at 50°C for 2 min (Kaur et al 2015a). Parameters recorded were pasting temperature (PT), peak viscosity (PV), breakdown viscosity (BDV), final viscosity (FV), and setback viscosity (SBV).…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Noodles were prepared following the method described earlier (Kaur et al 2015a). Cooking time (CT) was determined by cooking 5 g noodles in 100 ml boiling distilled water till the disappearance of white core as judged by squeezing between two glass slides.…”
Section: Noodle-making Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Textural properties of starch noodles have been reported to be influenced with amylose content as well as the incorporation of hydrocolloids (soluble fiber such as gums). Kaur, Shevkani, Singh, Sharma, and Kaur (2015) reported that noodles prepared from flour containing starches high in amylose have higher values of firmness than the noodles made from flour containing low amylose.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…Starch (3 g sample in 25 ml distill water) was weighed directly in the aluminium RVA sample canister and distilled water was added to a total constant sample weight 28 g. A programmed heating and cooling was used where samples were held at 50°C for 1 min, heated to 95°C in 7.5 min, held at 95°C for 5 min, cooling from 95°C to 50°C in 7.5 mins and holding at 50°C for 2 mins. Parameters recorded were pasting temperature, peak viscosity (PV), breakdown viscosity (BV), setback viscosity (SBV) and final viscosity (FV) (Kaur et al 2015).…”
Section: Apparent Amylose Contentmentioning
confidence: 99%